Effect of Risperidone on Liver Enzymes Levels in Children with Autism Spectrum Disorder - Shimul, Shahanaz Khan; Shahjadi, Shorifa; Naznin, Tahmina; Patwary, Md Shaiful Islam (Journal of Bangladesh Society of Physiologist, 2024)
Background: Irritability and hyperactivity are associated co-morbidities in autism spectrum disorder (ASD). Recently for this purpose, risperidone, an atypical antipsychotic is the drug of choice for ASD children. Abnormalities of liver enzymes were found associated with atypical antipsychotics. Methods: This observational study was conducted in the Department of Physiology, BSMMU carried on 68 children enrolled from parents forum, Mohakhali, Dhaka.All were diagnosed case of ASD with similar age and sex. Among them 34 were treated with risperidone which constituted the study group and 34 were not treated with risperidone constituted the control group. The enzymes were estimated by ELISA and automated analyzer. For statistical analysis student’s unpaired t-test was done. Results: The mean valuesof serum alkaline phosphatase (ALP), alanine aminotransferase (ALT), aspartate aminotransferase (AST) and gamma-glutamyl transferase (GGT)level of children with autism spectrum disorder who were treated with risperidone were significantly higher compared to control group. Conclusion: Risperidone adversely affects liver function by increasing enzymes level in children with autism spectrum disorder. J Bangladesh Soc Physiol 2023;18(2): 72-77